Slope Improvement using Combination of Coconut Husks, Coconut Flakes, Luffa, Pineapple Leaves and Vege-Grout - Omar R.C.; Roslan R.; Taha H.; Wahab W.A.; Baharuddin I.N.Z. (Mattingley Publishing, 2023)
Agricultural wastes; Erosion; Geotextiles; Grouting; Safety factor; Soils; Sustainable development; Waste treatment; Economic resources; Future generations; Luffa; Pineapple leaves; Site observation; Slope improvement; Soil erosion; Tensile reinforcement; Mortar